A High Enrichment Replenishment Rate Reduces Damaging Behaviors and Increases Growth Rate in Undocked Pigs Kept in Fully Slatted Pens - Chou, Jen-Yun; Sandercock, Dale A.; D'Eath, Rick B.; O'Driscoll, Keelin (Frontiers in Veterinary Science, 2020)
One of the difficulties in complying with the prohibition of routine tail docking is a lack of effective alternative solutions to prevent tail biting, especially in fully slatted systems. This study compared three slat-compatible enrichment replenishment strategies for pigs. Forty-eight mixed-sex pens (6 males and 6 females/pen) of undocked pigs were followed from birth to slaughter. Pre-weaning, half the pigs were provided with enrichment materials (a cardboard cup, rubber toy, hessian cloth and bamboo), in addition to a rope for the sows, in all farrowing crates. Post-weaning, all pens were enriched with 8 identical items, including an elevated rack supplied with fresh-cut grass, and objects of wooden, bamboo, rubber and fabric materials presented in various ways. However, three different replenishment frequencies were applied: “Low” (replenished on Monday/Wednesday/Friday), “Medium” (replenished once daily), and “High” (replenished ad libitum). Individual pigs were weighed on days 0, 49, 91 and 113 post-weaning. Direct behaviour observations were conducted twice weekly at pen level (10 min/day/pen), and tail and ear lesion scores of individual pigs were also recorded every other week. These measurements were taken during the post-weaning period. The cost of all enrichment materials used was calculated. Pre-weaning enrichment only contributed to a lower ear lesion score (P = 0.04). No difference in lesion scores was found between post-weaning treatments. “Low” replenishment rate pigs performed more damaging behaviours (tail / ear biting, belly-nosing, mounting, other biting and aggressive behaviours combined) than “High” and “Medium” pigs (P < 0.01). The average daily gain in the finishing stage was higher in “High” than “Low” pigs (P < 0.05). Although sporadic tail biting occurred, only 0.69% of the pigs had their tails bitten severely enough that they became shorter than half of a normal undocked tail. The average enrichment cost for the post-weaning period was less than €2 per pig. In conclusion, the high enrichment replenishment rate increased growth and reduced damaging behaviours compared to the low replenishment rate pigs. Overall, these findings show that the provision and regular replenishment of multiple, slat-compatible, enrichment sources can reduce tail damage to manageable levels without the need for tail docking.